The new innovative - integration mechanisms in the sphere of the science, education and business - Georgy. V. Korshunov; Daniil.O. Yuriev (Moscow Polytechnic University, 2022)
The article dwells upon one of the most effective tools for establishing the relationships between science, education and business - the project «UTime news». Realization of this project enables to join the efforts of science, education and business in order to improve co-development of research, educational process and production. The main results and plans for further development are briefly outlined here.